PENGARUH RASIO HUTANG DAN RASIO LANCARTERHADAP PROFITABILITAS PADA PT TELEKOMUNIKASI INDONESIA (PERSEROAN) TBK DATA DIAMBIL DARI LAPORAN KEUANGAN BEI PERIODE 2008-2016 - Handini Anjarianti Fauziah (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
The aim of this research is for knowing the effect of Debt to Equity Ratio and Current Ratio to Return on Assets at PT. Telekomunikasi Indonesia Tbk. period 2007 up to 2015. The data used taken from Financial statement data PT. Telkom, Published through the website www.idx.go.id. The direction of this research is for identify and explain the effect of Debt Ratio (DER) and Likuidity (CR) to Profitability (ROA) at PT. Telekomunikasi Indonesia Tbk. period 2008-2016 listed on Indonesia Stock Exchange (BEI). The analitical tool used in this research is using Multiple Regression Analysis. The sample used is quarter time series data during 9 periods as many as 36 financial statement report. Result of multiple regression analysis showing that debt ratio (DER) and liquidity (CR) significantly not effect to profitability. Amount of adjusted R-Squared is 0.054 which mean ROA being able to explain by independent variabel researched at 5,4% and remaining 94,6% affected by variabel not examined in this researched. Keyword: Debt Ratio, Current Ratio, Profitability